METROPOLITAN EDISON COMPANY: RESTRICTION ON DIVIDENDS ON COMMON STOCK; CONSENT ORDER. - Fisher, Allan J. (The Accounting Review, 1941)
The article focuses on a court case involving Metropolitan Edison Co. related to restriction on dividends on common stock. A recent release of the U.S. Securities and Exchange Commission under the Holding Company Act raises several significant issues with respect to the reclassification of surplus and the legality and financial advisability of dividends on common stock. The Metropolitan Edison Co. is a Pennsylvania corporation and a public utility operating company doing business in eastern Pennsylvania. It is a direct subsidiary of NY PA NJ Utilities Co., which is controlled by the Associated Gas and Electric Corp., which in turn is controlled by the Associated Gas and Electric Co. A series of resolutions adopted by the board of directors of the Metropolitan Edison Company resulted in the transfer of $6,111,333.00 from earned surplus to stated value of common stock between 1925 and 1931. The Securities and Exchange Commission on December 1, 1939, issued an order to the Metropolitan Edison Co. to show cause why an order should not be entered to prevent the declaration and payment of dividends on its capital stock.